2014
DOI: 10.1016/j.healthplace.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inequalities: What is the evidence for the effect of the neighbourhood food environment?

Abstract: This review summarises the evidence for inequalities in community and consumer nutrition environments from ten previous review articles, and also assesses the evidence for the effect of the community and consumer nutrition environments on dietary intake. There is evidence for inequalities in food access in the US but trends are less apparent in other developed countries. There is a trend for greater access and availability to healthy and less healthy foods relating to better and poorer dietary outcomes respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
231
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(249 citation statements)
references
References 105 publications
13
231
1
4
Order By: Relevance
“…1 Offspring ovarian reserve markers across categories of maternal neighborhood-level SES (education, poverty), adjusted for covariates and early childhood environments, suggesting particular exposures during these sensitive periods may shape trajectories of ovarian aging. Exposures related to maternal nutritional stress and maternal smoking, which are also significantly correlated with lower SES [76][77][78], are strong candidates for inclusion in future research to address whether maternal neighborhood-level SES in the current study may be marking behavioral, anthropometric, or other health-related characteristics of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…1 Offspring ovarian reserve markers across categories of maternal neighborhood-level SES (education, poverty), adjusted for covariates and early childhood environments, suggesting particular exposures during these sensitive periods may shape trajectories of ovarian aging. Exposures related to maternal nutritional stress and maternal smoking, which are also significantly correlated with lower SES [76][77][78], are strong candidates for inclusion in future research to address whether maternal neighborhood-level SES in the current study may be marking behavioral, anthropometric, or other health-related characteristics of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…49 Among 31 articles using measures of density (e.g., presence or number of food outlets within a specified area), 20 of the studies identified at least one significant positive association between density and diet in the expected direction (e.g., greater density of green grocers is associated with better dietary quality). Thirteen of 24 articles reviewed had no significant association between proximity (distance from the participant's home to the food outlet) and diet.…”
Section: Community Nutrition Environmentmentioning
confidence: 99%
“…49 Eleven studies examined 38 possible relationships between in-store availability of foods and dietary quality and found only 9 associations in the expected direction as well as 2 in the unexpected direction. Price yielded an even more complicated story -28 outcomes were examined and 12 demonstrated no relationships with price, five showed relationships in the expected direction, and 11 reported relationships in the unexpected direction (that better diets were associated with healthy foods being more expensive).…”
Section: Consumer Nutrition Environmentmentioning
confidence: 99%
See 2 more Smart Citations